Coffeehouse as Classroom: Examination of a New Style of Active Learning Environment. (March 2014) - Morrone, Anastasia S.; Ouimet, Judith A.; Siering, Greg; Arthur, Ian T.
Abstract : This chapter explores whether a new learning space, designed to be more like a café than a classroom, provides an environment that facilitates active and collaborative learning.